The Impact of Village Public Service Transformation Policy Implementation on SDGs Achievement: A Study of Village Governments in Banyumas Regency - Ranjani Ranjani; Tissa Silvia (Spirit Publik: Jurnal Administrasi Publik, 2026)
The acceleration of globalization and modernization requires traditional villages to transform to face structural and ecological challenges. This study aims to analyze the impact of the implementation of village public service transformation policies on the achievement of Sustainable Development Goals (SDGs) in Banyumas Regency. Through a descriptive quantitative approach, primary data were collected from 76 respondents consisting of village officials and related stakeholders using a Likert-scale questionnaire. Data analysis was conducted using logistic regression techniques using the Python programming language. The results indicate that descriptively, the implementation of public service transformation is in the fairly good category, but hypothesis testing revealed no statistically significant effect on SDG achievement. This is evidenced by a p-value of 0.5478 (> 0.05) and a very low Pseudo R2 (McFadden) value of 0.0040. These findings indicate a "broken link" between administrative modernization and real welfare indicators. The main obstacles identified include discrepancies in human resource competencies, limited digital infrastructure, and institutional inertia. This study concludes that service transformation at the village level remains procedural and has not significantly driven sustainable development targets. Substantial capacity building and more inclusive public participation are needed for village autonomy to have a real impact on achieving the SDGs.